Implementing Predictive Maintenance Strategy for Infrastructure in the ECRL Project Operation Phase - Mohamad Safwan Na'im Ridzuan; Joewono Prasetijo; Firdaus Abd Rahman (Progress in Engineering Application and Technology, 2025)
East Coast Rail Link (ECRL) project is one of the most recent railway project in Malaysia that is on the verge of approaching its operation phase in 2027. Revolving solely around traditional maintenance approaches and absence of predictive maintenance (PdM) approach within its current infrastructure maintenance strategy is a missed opportunity to potentially address the short daily maintenance interval and overcome unforeseen obstacles to the project’s long term viability. Hence. this paper addresses the potential of infrastructure maintenance strategy based on PdM implementation in the project’s operation phase. It synthesized various past studies regarding PdM, as semi-structured interviews comprising of multiple sections were utilised for gaining the insights and views of technically experienced individuals within the project. Results showed partcipants’ understanding and high regards towards PdM’s technology and capability, addressing its potential of implementation based on the aspects of ECRL Project. However, several barriers that constraint its adoption were highlighted intensively by each participant such as skill gaps, organizational readiness varies and multinational coordination challenge. Ultimately, the majority agreed on the need of investment and resource commitment from the top leadership on addressing these barriers.